WHAT IS CLIMATE CHANGE DOING TO US AND FOR US?: with Karl E. Peters, "Living with the Wicked Problem of Climate Change"; Paul H. Carr, "What Is Climate Change Doing to Us and for Us?"; James Clement van Pelt, "Climate Change in Context: Stress, Shock, and the Crucible of Livingkind"; Robert S. Pickart, "Climate Change at High Latitudes: An Illuminating Example"; Emily E. Austin, "Soil Carbon Transformations"; David A. Larrabee, "Climate Change and Conflicting Future Visions"; Panu Pihkala, "Eco‐Anxiety, Tragedy, and Hope: Psychological and Spiritual Dimensions of Climate Change"; Carol Wayne White, "Re‐Envisioning Hope: Anthropogenic Climate Change, Learned Ignorance, and Religious Naturalism"; Matthew Fox, "Climate Change, Laudato Si', Creation Spirituality, and the Nobility of the Scientist's Vocation"; Christopher Volpe, "Art and Climate Change: Contemporary Artists Respond to Global Crisis"; Jim Rubens, "The Wicked Problem of Our Failing Social Compact"; and Peter L. Kelley, "Crossing the Divide: Lessons from Developing Wind Energy in Post‐Fact America.". Issue 2 (June 2018) - Carr, Paul H.
Abstract: What are we doing to our climate? Emissions from fossil fuel burning have raised carbon dioxide concentrations 35 percent higher than in the past millions of years. This increase is warming our planet via the greenhouse effect. What is climate change doing to and for us ? Dry regions are drier and wet ones wetter. Wildfires have increased threefold, hurricanes more violent, floods setting record heights, glaciers melting, and seas rising. Parts of Earth are increasingly uninhabitable. Climate change requires us to act as a global community. Climate justice enjoins emitters to pay the social‐environmental costs of fossil fuel burning. This would expedite green solar, wind, and next‐generation nuclear energy sources. Individuals should conserve resources, waste less food, and eat a plant‐rich diet.